Occult contralateral nodal disease in oropharyngeal squamous cell carcinoma patients undergoing primary TORS with bilateral neck dissection. (June 2019) - McMullen, Caitlin P.; Garneau, Jonathan; Weimar, Emillie; Ali, Sana; Farinhas, Joaquim M.; Yu, Eugene; Som, Peter M.; Sarta, Cathy; Goldstein, David P.; Su, Susie; Xu, Wei; Smith, Richard V.; et al.
Highlights: Occult contralateral nodal disease rate in surgically-managed HPV+ OPSCC is not definitively known. Multi-institutional population of resectable oropharyngeal cancers. Occult contralateral nodal metastases rate was low (7.4% in the entire cohort; 5% in the p16+ cohort). Abstract: Background: Knowledge of the rate of occult contralateral nodal disease for oropharynx cancers (OPSCC) in the era of Human Papillomavirus-dominated disease would inform practitioners as to who may be a candidate for unilateral neck management. The objective of this study was to determine the rate of pathologic contralateral positive nodes in patients in OPSCC patients with pT1 and pT2 disease treated with TORS and bilateral neck dissections (BND). Methods: Retrospective review of medical records was performed at Princess Margaret Cancer Center, Toronto; Icahn School of Medicine at Mount Sinai, New York City; and Montefiore Medical Center, New York City. Patients with pT1-2 N0-3 (AJCC 8th Edition) OPSCC disease treated with TORS and BND were included. Results: Thirty-two patients met inclusion criteria. Twelve patients (37.5%) had a tonsil primary site, 19 (59.4%) patients had a base of tongue primary site, and 1 (3.1%) patient had a pharyngeal wall primary. Twenty-four (75%) patients were known to be p16+. Twenty-seven patients (84.4%) were radiographically negative in the contralateral neck preoperatively, and two of these patients had pathologic contralateral positive nodes. The occult pathologic contralateral nodal metastasis rate was 7.4% (2/27). The sensitivity, specificity, positive predictive value, and negative predictive value of suspicious contralateral nodes on preoperative imaging for pathologically positive nodes were 33.3%, 86.2%, 20% and 93% respectively. In the p16+ subgroup, the occult nodal positive rate in the contralateral neck was 5%. Conclusions: pT1-2 OPSCC patients undergoing TORS and elective contralateral neck dissection have a low rate of pathologic contralateral nodal positivity.